A service-oriented infrastructure for collaborative learning in virtual knowledge spaces - Bopp, Thomas (2006)
Classical knowledge production is an author-centered process. The emergence of cooperative internet technologies such as wikis or blogs shows a shift towards stronger cooperative production and communication of knowledge, closing the gap between readers and authors. The incorporation of such participatory mechanisms into CSCL/CSCW systems raises several new requirements. We present an open service infrastructure that provides an architecture meeting these demands, while integrating itself into a network of already-established services.